y=2x+3 y=3x+10
how to solve this substitution method problem that are both in function form
1) y=2x+3
2) y=3x+10
Substitute the right side of equation two, which is the value of y,
for the left side of equation equation one.
3x + 10 = 2x + 3
3x + 10 - 2x = 2x + 3 - 2x
x + 10 = 3
x + 10 - 10 = 3 - 10
x = -7
Now, you have a value for x that you can
substitute into either of the two equations.
y = 2x + 3
y = 2(-7) + 3
y = -14 + 3
y = -11
To verify the answers, substitute them
into the other equation.
y = 3x + 10
-11 = 3(-7) + 10
-11 = -21 + 10
-11 = -11